Facile Synthesis of Guanidine Functionalised Building Blocks. Issue 4 (19th January 2015) - Hickey, Shane M.; Ashton, Trent D.; Pfeffer, Frederick M.
Abstract Three useful developments in the preparation of guanidines are presented herein. A collection of bis(Boc)aminoalkylguanidines (n=2, 3, 4 and 6; Boc=tert‐butoxycarbonyl), known to be prone to cyclisation, have been synthesised and isolated without chromatography as shelf‐stable sulfonate salts in good yield (up to 94 %). Secondly, a selection of guanidines tethered to a range of other functional groups, including alkyne, alkene, alcohol, and azide, have been prepared in good yields with no requirement for a purification step, and thirdly an inexpensive, high‐yielding (93 %), and facile synthesis of N, N′‐bis(Boc)guanidine, a key precursor for N, N′‐bis(Boc)‐N′‐triflylguanidine, is described in which the need for chromatographic purification is again obviated.